1990
DOI: 10.1017/s0033291700017025
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological deficits and CT scan changes in elderly depressives

Abstract: SynopsisA number of computerized tests were used to study visual attention, memory and learning in elderly depressed patients. Impairment was found in approximately 70% of depressed patients and was seen particularly in memory and in measures of latency. Depressed patients showed equivalent impairment in short-term memory but less impairment in conditional associative learning compared to a group of patients with early dementia of the Alzheimer-type (DAT), matched for age and pre-morbid IQ. With respect to qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
167
1
8

Year Published

1995
1995
2007
2007

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 263 publications
(189 citation statements)
references
References 49 publications
13
167
1
8
Order By: Relevance
“…Our laboratory has preliminary findings that the anticholinergic antidepressant amitriptyline impairs IT in healthy subjects. However, there have been mixed findings of the effects of medication on neuropsychological function in depressed patients (Glass et al 1981 ;Abas et al 1990). A study by Spring et al (1992) indicated that the adverse cognitive effects of amitriptyline were observed only after depressive symptoms had improved.…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory has preliminary findings that the anticholinergic antidepressant amitriptyline impairs IT in healthy subjects. However, there have been mixed findings of the effects of medication on neuropsychological function in depressed patients (Glass et al 1981 ;Abas et al 1990). A study by Spring et al (1992) indicated that the adverse cognitive effects of amitriptyline were observed only after depressive symptoms had improved.…”
Section: Discussionmentioning
confidence: 99%
“…These impairments include deficits in tasks sensitive to hippocampal dysfunction: visual delayed match-to-sample 46 and verbal learning. 3 Interestingly, the verbal learning impairment found in patients with chronic depression was correlated with the degree of reduction of hippocampal grey matter found using magnetic resonance imaging.…”
Section: Molecular Mechanisms Underlying the Ecs Effectmentioning
confidence: 99%
“…The main guiding principles have been to use some tests that can be related to the extensive neuropsychological literature in animals and to employ tests that can be broken down into their cognitive components in order to define more readily which functions are impaired and which are spared. The battery has now been used quite extensively in the testing of patients with Alzheimer's disease and other forms of dementia (Sahakian et al, 1988Sahgal et al, 1991Sahgal et al, ,1992, patients with basal ganglia disorders such as Parkinson's disease (Downes et al, 1989;Owen et al, 1992, Korsakoff's syndrome (Joyce & Robbins, 1991), depression (Abas et al, 1990;Beats et al, 1996), schizophrenia , HIV-positive patients , and children with minimal learning disabilities or autism (Hughes et al, 1994). The tests have also been validated in neurosurgical patients with excisions of the temporal or frontal lobes and amygdalohippocampectomy (Owen et al, 1995).…”
Section: Introductionmentioning
confidence: 99%